Does the technology acceptance model predict actual use? A systematic literature review - Turner, Mark; Kitchenham, Barbara; Brereton, Pearl; Charters, Stuart; Budgen, David (Information and software technology, 2010)
The technology acceptance model (TAM) was proposed in 1989 as a means of predicting technology usage. However, it is usually validated by using a measure of behavioural intention to use (BI) rather than actual usage. This review examines the evidence that the TAM predicts actual usage using both subjective and objective measures of actual usage. We performed a systematic literature review based on a search of six digital libraries, along with vote-counting meta-analysis to analyse the overall results. The search identified 79 relevant empirical studies in 73 articles. The results show that BI is likely to be correlated with actual usage. However, the TAM variables perceived ease of use (PEU) and perceived usefulness (PU) are less likely to be correlated with actual usage. Care should be taken using the TAM outside the context in which it has been validated.